Learning any Language with Linguoculturology Enriches our Knowledge and Broadens our Horizon - Samatova Zulhumor Qudratilla qizi (Zien Journals, 2022)
This article deals with the data related to one of the most crucial branches of the modern linguistics, linguoculturology.
Keywords: linguistics; culture; linguoculturology; communication